2018
DOI: 10.1007/s11199-017-0877-1
|View full text |Cite
|
Sign up to set email alerts
|

When Job Ads Turn You Down: How Requirements in Job Ads May Stop Instead of Attract Highly Qualified Women

Abstract: Qualification-based targeted recruitment strategies aim to increase the number of qualified applicants from certain social groups, such as women. Typically, such strategies assume that individuals are more likely to apply for a job when they possess the requirements needed for that job. However, how job seekers react to requirements in job ads is not often considered and is explored in the present study. In two experimental studies with Belgian university students we investigated whether person requirements ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 58 publications
2
32
0
Order By: Relevance
“…In line with assumptions from the LC‐model (Semin & Fiedler, 1991), ads that included negatively metastereotyped personality requirements were perceived as more attractive if such traits were worded in a behavioural way compared with a dispositional way. Similar findings were reported among ethnic minority and female job seekers (Wille & Derous, 2017, 2018) and seem to uphold for other groups of job seekers that might suffer from stereotypes and stigmatization on the labour market, like older/younger job seekers.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In line with assumptions from the LC‐model (Semin & Fiedler, 1991), ads that included negatively metastereotyped personality requirements were perceived as more attractive if such traits were worded in a behavioural way compared with a dispositional way. Similar findings were reported among ethnic minority and female job seekers (Wille & Derous, 2017, 2018) and seem to uphold for other groups of job seekers that might suffer from stereotypes and stigmatization on the labour market, like older/younger job seekers.…”
Section: Discussionsupporting
confidence: 80%
“…Second, not only whether , but also how negatively metastereotyped personality requirements in job ads affect job attraction is not well understood. Consistent with stereotype threat literature (Steele & Aronson, 1995), studies suggested—but did not test—whether stereotyped information in job ads might elicit threat, which in turn may lead to a loss of interest in the advertised job (Wille & Derous, 2017, 2018). Alternatively, Finkelstein et al (2020) recently showed that negative metastereotypes might also trigger perceptions of challenge and possibly result in more positive recruitment outcomes.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In [38], the authors examined soft skills required by women and men in job ads and found that soft skills are associated with gender segregation across occupations and reinforce wage inequalities between men and women by rewarding typically "male" characteristics and penalizing "female" traits. In [139], the authors examined how job seekers react to requirements in job ads. More precisely, they investigated the impact of job requirements on women's job attraction and decision to apply.…”
Section: ) Gender Biasmentioning
confidence: 99%
“…Organizations have different opportunities to signal their level of diversity to applicants (e.g. via diversity-sensitive job ads, advertising campaigns, or role models; Ford and Patterson, 2019;Pietri et al, 2019;Wille and Derous, 2018). Following signaling theory, "applicants construe many recruitment-related activities and information as signals of unknown organizational characteristics" (Celani and Singh, 2011, p. 223); yet, activities and signals that are sent by organizations are only relevant if applicants receive and evaluate those signals.…”
Section: Board Composition and Employer Attractivenessmentioning
confidence: 99%